2011
DOI: 10.1038/ijir.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

On-demand use of erectile aids in men with preoperative erectile dysfunction treated by whole gland prostate cryoablation

Abstract: Prostate cryoablation is an established minimally invasive treatment for localized prostate cancer (PCa). However, the impairment of erectile function (EF) is considered a serious complication of the procedure. To investigate the efficacy of erectile aids following cryotherapy, 93 patients who underwent whole gland prostate cryoablation with required complete medical records were analyzed. The changes in postoperative EF were evaluated using the International Index of Erectile Function (IIEF-5) questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The visualized leading edge of the ice at the periphery of the ice ball is just below freezing (08C), and the isotherms for temperature change in tissues show that lethal temperatures (À408C) exist at least 5 or more millimetres inside the leading edge of the ice. Several groups of investigators have reported profound loss of sexual function in patients after whole-gland prostate cryoablation, due to collateral neurovascular damage [10][11][12]. At this distance, collateral damage to the rectal wall and neurovascular structures is a serious concern during prostate cryoablation, despite major efforts to minimize the risk.…”
Section: Cryotherapymentioning
confidence: 99%
“…The visualized leading edge of the ice at the periphery of the ice ball is just below freezing (08C), and the isotherms for temperature change in tissues show that lethal temperatures (À408C) exist at least 5 or more millimetres inside the leading edge of the ice. Several groups of investigators have reported profound loss of sexual function in patients after whole-gland prostate cryoablation, due to collateral neurovascular damage [10][11][12]. At this distance, collateral damage to the rectal wall and neurovascular structures is a serious concern during prostate cryoablation, despite major efforts to minimize the risk.…”
Section: Cryotherapymentioning
confidence: 99%